From contract to status in quest for security - Adeogun, A. A. (Yaba, Lagos, Nigeria : Lagos University Press, 1986)
This book deals with the 19th century -laissez-faire which rested on two legs-the freedom and the sanctity of contracts.
"An inaugural lecture delivered at the University of Lagos on Wednesday, 9th April, 1986."
Includes bibliographical references: p. 54-60.
oo 12/04/2019
Loans
Keywords: Labor laws and legislation; Nigeria